The role of trust in online shopping behavior - Jadehkenari, Marzieh Zendehdel; Paim, Laily (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The increase of the rate of internet usage has significantly influenced the people’s life style, in general, and the consumers’ intentions towards online shopping behavior, in particular. The objective of this study is to explore three dimensions of trust that affect consumers’ attitude towards online shopping and online shopping intention in Malaysia. The model of this study was developed in the light of the Theory of Reasoned Action (TRA) and the data were collected from 375 students in Klang Valley area. Using structural equation modeling as the approach to examine the model, the statistical results confirmed the positive effect of integrity and ability towards online shopping attitude, however there is no significant in consumers’ attitude towards online shopping based on benevolence.